Corpos no armário: performances narrativas das masculinidades e travessias homoeróticas na fronteira - Melo, Thiago Benitez de (2023)
The goal of this research, located in the Triple Frontier of Iguaçu, was to investigate the constructions of the narrative performances of masculinities (BUTLER, 2003; CONNELL, 2003) from masking strategies of homoerotic sexuality, through border crossings (BrazilArgentina/Brazil-Paraguay) of men who have sex-affective relationships with other men, seeking to understand the formation of discourses focusing on “coming in and out of the closet” (SEDGWICK, 2007). I sought to analyze, understand and discuss accounts of dissident sexual experiences (BENTO, 2006; LOURO, 2004) narratives and life stories through onlineOffline conversations (MOITA LOPES, 2020), both virtual and face-to-face, before, during and after the Covid-19 pandemic, with users of the relationship app Grindr, focusing on subjects who cross borders in search of homoerotic practices. This research is part of the broad field of study of the humanities, following guidelines towards transgression and breaking with disciplinary boundaries, towards an inter/trans/indisciplinary perspective (MIGNOLO, 2008; MOITA LOPES, 2006), under the light of multi-situated and moving ethnography (PEIRANO, 2014; MARCUS, 1995; RAMOS, 1990). The justification for this thesis was based on the importance of discussing issues focused on the bodies and desires that were placed underground (POLLAK, 1989) for being seen as “deviant” (BECKER, 2008), in addition to having their practices and experiences taken as infamous and abject (PINHEIRO, 2018), which, consequently, silenced, denied, concealed and threw into the private sphere these ways of knowing how to live. These subjectivities have been made invisible and reviled over the years by hegemonic discourses: religious, political-legal, biological-scientific, patriarchal family, school, media, among others (FOUCAULT, 2004). By analyzing the indexical processes (SILVERSTEIN, 2009), of entextualization (BAUMAN and BRIGGS, 1990) and linguistic cues (BLOMMAERT, 2010) involved in the construction of narrative performances of secrecy strategies (MISKOLCI, 2017), it is argued that, for fear of prejudice, reprisals and abandonment, many men who relate sexually and affectively with other men use cybernetic space as a hiding place (a “virtual closet”) for their homoerotic practices, performing heteronormative masculinities (such as the cult of the muscular body) and crossing borders (even in times of social isolation) in order not to be recognized in their territory of origin, a kind of sexile (GUZMÁN, 1997). Therefore, non-masculinist gender performances and sexual practices that escape the hegemony of heterocisnormativity still end up suffering processes of rejection and exclusion.